Figures of the Young Actress in the Dramatic Art of A.N. Ostrovsky and A.P. Chekhov - Regéczi, Ildikó (Slavica, 2021)
The present study focuses on the turning point in drama history between the artistic concept of A.N. Ostrovsky, the founder of modern Russian theater, and that of A.P. Chekhov, who transformed the former approach in the matter of just a few decades. I propose that an analysis of Ostrovsky’s Talents and Admirers (1881) and Chekhov’s The Seagull (1896) can reveal the borderline that divides the dramatic formations belonging to these two separate periods. The analysis concentrates on the transformation of a specific motive, the portrayal and the dramatization of the chances of destiny available for the figure of the young actress. I presume that the dramaturgical features surfacing through the exploration of this portrayal will outline the differences in the approach and in the poetic means used by the outstanding representatives of these successive periods in drama history. Thus, I am not seeking intertextual instances in the narrow sense of the term. Rather, I am after a thematic and motive-based congeniality and its saturation with a new meaning, coming from the functional shift that establishes a connection between the texts of the pieces by Chekhov and Ostrovsky. This approach to intertextuality in the broader sense of the term, which is not primarily present in references at the textual level but is rather based on, for example, thematic congruity, can play an important part also in the assessment concerning functional history, in exploring reception-related peculiarities and, consequently, in the validation of the historical aspect.